Zastosowanie koncepcji controllingu w zarządzaniu współczesnym przedsiębiorstwem - Chomiak, Iwona (Using controlling conception in management contemporary companies, 2005)
This article presents possibilities in using controlling conception as a contemporary tool supporting management process in companies. In this way the article talks over the essence of controlling conception and indicates departments of company which make use of controlling methods and tools in functioning.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 189-198